2022
DOI: 10.1002/alz.063223
|View full text |Cite
|
Sign up to set email alerts
|

Novel Wnt modulators for the treatment of Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is the most common form of age‐related dementia characterized by the presence of amyloid‐β (Aβ) and tau pathologies leading to neurodegeneration and cognitive impairment. Wnt/β‐catenin signaling modulates multiple pathophysiological processes including synaptic plasticity, neuronal survival, neuroinflammation, Aβ production and tau phosphorylation, but this signaling pathway is greatly inhibited in the AD brain. Notably, two SNPs and an alternative splice variant of Wnt co‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We have reported that W2A-16 effectively mitigates amyloid pathology and cognitive decline in 5xFAD amyloid model mice. Furthermore, we have showed that W2A-16 reduces tau phosphorylation and neuroinflammation in PS19 tauopathy mice ( Li et al, 2022 ). Moreover, our recent unpublished data indicate that W2A-16 is also a novel potent class I HDAC inhibitor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that W2A-16 effectively mitigates amyloid pathology and cognitive decline in 5xFAD amyloid model mice. Furthermore, we have showed that W2A-16 reduces tau phosphorylation and neuroinflammation in PS19 tauopathy mice ( Li et al, 2022 ). Moreover, our recent unpublished data indicate that W2A-16 is also a novel potent class I HDAC inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanisms underpinning BBB maintenance and governing gene transcription remain elusive. We have developed a novel Wnt activator named W2A-16 ( Li et al, 2022 ), which is documented in World Intellectual Property Organization (WIPO) PatentScope database (WO2021007313). We have reported that W2A-16 effectively mitigates amyloid pathology and cognitive decline in 5xFAD amyloid model mice.…”
Section: Introductionmentioning
confidence: 99%